2016
DOI: 10.1038/cgt.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Regional CAR-T cell infusions for peritoneal carcinomatosis are superior to systemic delivery

Abstract: Metastatic spread of colorectal cancer (CRC) to the peritoneal cavity is common and difficult to treat, with many patients dying from malignant bowel obstruction. Chimeric antigen receptor T cell (CAR-T) immunotherapy has shown great promise, and we previously reported murine and phase I clinical studies on regional intrahepatic CAR-T infusion for CRC liver metastases. We are now studying intraperitoneal (IP) delivery of CAR-Ts for peritoneal carcinomatosis. Regional IP infusion of CAR-T resulted in superior p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 23 publications
3
111
0
Order By: Relevance
“…Thus, we postulate that, by applying an appropriate magnetic field gradient, the approach developed in this study could be useful to assess cell targeting to specific locations inside the body for cell‐based therapies. This study also suggests the possibility to realize cell retention in the peritoneal cavity using our nanoparticles, which may be interesting for applications such as cancer cell therapies if similar results are further obtained with different kind of therapeutic cells.…”
Section: Resultssupporting
confidence: 57%
“…Thus, we postulate that, by applying an appropriate magnetic field gradient, the approach developed in this study could be useful to assess cell targeting to specific locations inside the body for cell‐based therapies. This study also suggests the possibility to realize cell retention in the peritoneal cavity using our nanoparticles, which may be interesting for applications such as cancer cell therapies if similar results are further obtained with different kind of therapeutic cells.…”
Section: Resultssupporting
confidence: 57%
“…Other groups are exploring the possibility of local delivery, to enhance tumor killing and to reduce toxicity. Indeed, it has been shown that regional administration of anti-AFP or anti-CEA CAR T cells was equally effective or even superior to a systemic administration in xenograft models of peritoneal carcinomatosis (106,107), and the delivery of CAR T cells through percutaneous hepatic artery infusions has shown to be safe and clinically active in patients with CEA-expressing liver metastases (108). A different approach to favor the localization into the tumor site consists in the administration of CAR T cells overexpressing tumorspecific chemokine receptors enhancing their capacity of reaching the tumor tissues (109).…”
Section: Car T Cells For Solid Tumorsmentioning
confidence: 99%
“…Pre‐clinical studies have demonstrated that intraperitoneal infusion of CAR T‐cells is worthy of further study for peritoneal carcinomatosis. In a murine model for peritoneal carcinomatosis, we evaluated intraperitoneal infusion of CAR T‐cells compared with systemic infusion for CEA+ peritoneal tumors . Not only did the intraperitoneal CAR T‐cells protect against tumor re‐challenge intraperitoneally, it also protected against tumor at subcutaneous sites.…”
Section: Immunotherapy Solutions For Liver and Peritoneal Metastasesmentioning
confidence: 99%